2000
DOI: 10.1021/jf990648z
|View full text |Cite
|
Sign up to set email alerts
|

Development and Testing of Seven New Synthetic Coyote Attractants

Abstract: Available evidence indicates that effective coyote attractants are blends of volatile substances. Typically, attractants are a combination of biological substances such as fermented glandular materials, urines, and rotted meats. Although effective, these attractants have several distinct disadvantages. Among these is the possibility that they are unnecessarily complex and variable and, thus, difficult to replicate from one batch to the next. Although attractants containing a few reagent grade materials are ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 8 publications
(7 reference statements)
2
25
0
Order By: Relevance
“…Briefly, experimental groups (2011: n = 4; 2013: n = 4) received the odor cues four times over a 20‐day period, whereas control pairs (2011: n = 4; 2013: n = 4) received water as a delivery control (Schell et al, ). Our initial study did not have an outgroup odor; however, previous studies indicate that coyote behavioral responses toward other chemical attractants are characteristically similar to the behavioral responses we observed in our previous work (Kimball, Johnston, Mason, Zemlicka, & Blom, ; Kimball, Mason, Blom, Johnston, & Zemlicka, ; Schell et al, ; Shivik, Wilson, & Gilbert‐Norton, ). We did not find a statistical effect of our odor manipulation on subsequent parenting behavior (Schell et al, ) or prolonged hormonal effects (Schell et al, ).…”
Section: Methodssupporting
confidence: 78%
“…Briefly, experimental groups (2011: n = 4; 2013: n = 4) received the odor cues four times over a 20‐day period, whereas control pairs (2011: n = 4; 2013: n = 4) received water as a delivery control (Schell et al, ). Our initial study did not have an outgroup odor; however, previous studies indicate that coyote behavioral responses toward other chemical attractants are characteristically similar to the behavioral responses we observed in our previous work (Kimball, Johnston, Mason, Zemlicka, & Blom, ; Kimball, Mason, Blom, Johnston, & Zemlicka, ; Schell et al, ; Shivik, Wilson, & Gilbert‐Norton, ). We did not find a statistical effect of our odor manipulation on subsequent parenting behavior (Schell et al, ) or prolonged hormonal effects (Schell et al, ).…”
Section: Methodssupporting
confidence: 78%
“…Novel odors elicit both rub-rolling and scent-marking in carnivores (Kleiman 1966, Reiger 1979, Scrivner et al 1987, Phillips et al 1990, Kimball et al 2000. The proportion of coyotes exhibiting rub-rolling and scent-marking following removal of treatments was similar between large and small cones.…”
Section: Discussionmentioning
confidence: 99%
“…Phillips et al (1990) and Windberg (1996) found no differences between genders when testing responses of individual coyotes to novel visual and olfactory stimuli. However, Kimball et al (2000) tested male-female pairs of coyotes and found females were often first to approach and spent longer periods interacting with novel olfactory attractants, which suggests that the presence of a mate may influence individual coyote responses to novel stimuli, and hence, potentially influence response to the removal of a novel object. Because previous studies have not compared responses to novelty by solitary individuals and individuals in mated pairs, we also evaluated the effect of these variables on responses of coyotes to novel objects and their removal.…”
mentioning
confidence: 99%
“…The response evoked by each lure generally depends on whether it is sexual or gustatory in nature. Synthetic canid lures, such as those identified by the U.S. Department of Agriculture, can offer an effective and relatively consistent tool in evoking a required response, such as visitation to a trap or bait station (Kimball et al 2000). Recent pen trials undertaken by Pestat Ltd (www.pestat.com.au) on captive red foxes showed that one synthetic lure in particular, synthetic fermented egg (Bullard et al 1978), was a particularly powerful fox attractant (Figure 1).…”
Section: Aerosolized Synthetic Luresmentioning
confidence: 99%